2022
DOI: 10.1002/rmv.2401
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus (HEV) open reading frame 2: Role in pathogenesis and diagnosis in HEV infections

Abstract: Hepatitis E virus (HEV) infection occurs worldwide. The HEV genome includes three to four open reading frames (ORF1‐4). ORF1 proteins are essential for viral replication, while the ORF3 protein is an ion channel involved in the exit of HEV from the infected cells. ORF2 proteins form the viral capsid required for HEV invasion and assembly. They also suppress interferon production and inhibit antibody‐mediated neutralisation of HEV, allowing the virus to hijack the host immune response. ORF2 is the only detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 149 publications
(392 reference statements)
0
2
0
Order By: Relevance
“…Several other reports showed that HEV is excreted in the urine of HEV-3 and/or HEV-4-infected patients or non-human primates with evidence of kidney injury [ 24 , 39 ]. The replication of HEV in the kidney was confirmed by the detection of negative-strand HEV RNA, HEV ORF2 antigen, and other histopathological changes in known animal models such as pigs, non-human primates, rabbits, and Mongolian gerbils [ 24 , 26 , 40 , 41 , 42 ]. HEV is released in the urine, and the urine of HEV-infected monkeys was found to contain viral particles that were infectious to naïve monkeys [ 24 ].…”
Section: Discussionmentioning
confidence: 97%
“…Several other reports showed that HEV is excreted in the urine of HEV-3 and/or HEV-4-infected patients or non-human primates with evidence of kidney injury [ 24 , 39 ]. The replication of HEV in the kidney was confirmed by the detection of negative-strand HEV RNA, HEV ORF2 antigen, and other histopathological changes in known animal models such as pigs, non-human primates, rabbits, and Mongolian gerbils [ 24 , 26 , 40 , 41 , 42 ]. HEV is released in the urine, and the urine of HEV-infected monkeys was found to contain viral particles that were infectious to naïve monkeys [ 24 ].…”
Section: Discussionmentioning
confidence: 97%
“…Anemia was the most common observed side effect in first-line ribavirin therapy. Pegylated interferon-α has also been used successfully for HEV treatment but is associated with many adverse effects including cholestasis and teratogenicity [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%